Ko grem in se vrnem, objemam ves svet: Katalog k razstavi skupine W.O.R.M.S. v Univerzitetni knjižnici Maribor, 2. 7.–11. 9. 2021 (University of Maribor Press, 2021)
When I go and come back, I embrace the whole world. The experimental, avant-garde, multimedia artistic, also poetic and finally almost the most film group WORMS, active mainly in the past eighties and nineties, has its beginnings in 1983, when young artists joined forces in Maribor and were named first Worms or later in English. Worms. The founding ensemble - Gorazd Šifrer, Edmund Türk, Maja Jeričević, Dušan Ivanišin and Uroš Smasek - worked in the fields of photography, poetry, painting and film. She presented herself for the first time in January 1984 and with the participation of some co-creators - Andreja Pisnik, Vito Lužar ... - she participated in the first short feature films Krog in Danaja (inspired by Türk’s love poetry) and was awarded at all domestic and major foreign festivals of amateur or production-independent film.